2008
DOI: 10.1007/s00605-008-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud vector bundles

Abstract: We construct vector bundles R rk µ on a smooth projective curve X having the property that for all sheaves E of slope µ and rank rk on X we have an equivalence: E is a semistable vector bundle ⇐⇒ Hom(R rk µ , E) = 0. As a byproduct of our construction we obtain effective bounds on r such that the linear system |R · Θ| has base points on U X (r, r(g − 1)).⊗rR(g−1)−dR 1 . This implies that F itself is a semistable bundle of slope 2.1 Construction of S µ,R,m for µ ∈ [−g − 1, −g)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Some improvements on those results were obtained in [1,4]. Finally, [5] gave, at least theoretically, a characterization of all the points in the base locus (see also [6]). In sharp contrast with the degree zero case, not much has been done for other degrees, the main reason being that a characterization of fixed points was not available till the Strange Duality Conjecture was proved in [7] (see also [2]).…”
Section: Introductionmentioning
confidence: 91%
“…Some improvements on those results were obtained in [1,4]. Finally, [5] gave, at least theoretically, a characterization of all the points in the base locus (see also [6]). In sharp contrast with the degree zero case, not much has been done for other degrees, the main reason being that a characterization of fixed points was not available till the Strange Duality Conjecture was proved in [7] (see also [2]).…”
Section: Introductionmentioning
confidence: 91%
“…The specications for the construction are given in the proof below. For more details on F r,d and its properties see the article [9] (ii') There exists a vector bundle…”
Section: Semistability Conditions On Curvesmentioning
confidence: 99%
“…We can compute the rank and degree of R r,d in terms of the genus g Y of Y and the integers r and d (see Proposition 2.2 and Corollary 3.4 in [6]). …”
Section: Letmentioning
confidence: 99%
“…In [6], building on Popa's result it was shown that Raynaud bundles exist. In [3], an analog of Faltings' semistability criterion is given for parabolic vector bundles.…”
Section: Introductionmentioning
confidence: 99%